Dėl pašalio vietininkų Jokūbo Morkūno Postilėje - Maskuliūnas, Bronius (Baltistica, 2006)
ON THE POSTPOSITIONAL LOCATIVES IN POSTIL BY JOKŪBAS MORKŪNASThis article deals with some cases of use of the postpositional locatives - the adessive and the allative – found in the Postil published by Jokūbas Morkūnas in 1600. The studied material proves that the allative dominates considerably over the adessive in the Postil.The majority of the adessive forms are the singular adessives of the masculine gender. Other forms are also found but very few. About 60 % of the fixed adessive forms are pronominal, and they are more common than the nominal forms. In the Postil by Morkūnas the allative is much more frequent than the adessive. The nominal and the pronominal forms of the allative are almost equally used. The masculine singular allatives do not prevail here. There are quite a lot of feminine allatives, and plural allatives are rather often used.The preponderance of the allative is characteristic of all the Lithuanian writings of the 16th–17th centuries. This can partly be due to the rapid process of neutralization of the semantic functions of the adessive and the allative. In most cases the adessive was replaced by the allative as the latter was a more powerful case semantically. Another probable cause of the semantic weakness of the adessive is its neutralization and the concurrence of its syntactical functions with the inessive.
Keywords: lietuvių kalba; senieji raštai; pašalio vietininkas; Postilė